2012
DOI: 10.1039/c2an15924d
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigation of salivary calculi, by mid-infrared spectroscopy

Abstract: Sialolithiasis is common in salivary glands, especially in the submandibular and parotid ducts. X-Ray diffractometry was the principal technique used for their analysis, sometimes associated with scanning electron microscopy. Hydroxyapatite was the most frequently described constituent, in association with whitlockite and other calcium phosphates as brushite or octocalcium phosphate. Proteic matter was detected, as mucoproteins, albumin, nucleoproteins or as degenerative bacterial matter. This study presents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
2
20
1
Order By: Relevance
“…Teymoortash et al [18] analyzed sialoliths from Wharton's duct (a duct of the submandibular salivary gland) and discovered that the organic materials were predominantly concentrated in the outer shell of the stones and their components were glycoproteins, mucopolysaccharides, lipids, and cellular detritus (Phospholipids). Considerable research carried out by several groups such as Sabot et al in 2012 [19]; Szalma et al 2012 [20]; Faklaris et al 2013 [21]; and Kraaji et al 2014 [22]) have also advanced our understanding of stone architecture by showing that some can have a pure protein nucleus surrounded by mixed organic and carbonate apatite layers; whereas others can have internal layers of apatite covered by a dense and varnished crust of proteins and other organic compounds. In addition, Yiu et al [23] and Ho et al [24] recently reported that bone forming mechanisms involved in the early stages of kidney stone development and arterial calcification also require the participation of proteins and transcription factors.…”
Section: Protein Matrix Vs Organic Phase: Current Evidencementioning
confidence: 99%
“…Teymoortash et al [18] analyzed sialoliths from Wharton's duct (a duct of the submandibular salivary gland) and discovered that the organic materials were predominantly concentrated in the outer shell of the stones and their components were glycoproteins, mucopolysaccharides, lipids, and cellular detritus (Phospholipids). Considerable research carried out by several groups such as Sabot et al in 2012 [19]; Szalma et al 2012 [20]; Faklaris et al 2013 [21]; and Kraaji et al 2014 [22]) have also advanced our understanding of stone architecture by showing that some can have a pure protein nucleus surrounded by mixed organic and carbonate apatite layers; whereas others can have internal layers of apatite covered by a dense and varnished crust of proteins and other organic compounds. In addition, Yiu et al [23] and Ho et al [24] recently reported that bone forming mechanisms involved in the early stages of kidney stone development and arterial calcification also require the participation of proteins and transcription factors.…”
Section: Protein Matrix Vs Organic Phase: Current Evidencementioning
confidence: 99%
“…It has been reported that round stones often occur during the early phase of sialolithiasis, are generally small in size and shape, and are composed of a fairly round mineralized core surrounded by few concentric layers (Sabot et al , 2012). Owing to their high tendency for rolling and low strength of fixation to the ductal wall, round sialoliths are considered easily removable by surgical procedures (Yu et al , 2005; Luers et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The formation and development mechanisms of calculi have been explored, mainly from a microperspective, since the beginning of the 19th century (Sabot et al , 2012). Calculi development in the salivary extraglandular system frequently causes salivary gland obstruction, which manifests as pain and swelling (Jardim et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed knowledge of the composition of the sialoliths can contribute to a further understanding of the formation mechanism and possibly can provide the basis for dissolution or prevention of stone recurrence. Studies on the structural characterization of sialoliths include the use of FTIR spectroscopy, Raman microspectroscopy, thermal analysis, mass spectroscopy, X‐ray diffraction and X‐ray photoelectron spectroscopy . Since Lustman suggested his hypothesis that bacterial involvement in the etiology of sialoliths, the microstructural characterization of sialoliths through scanning electronic microscopy have gained considerable attention .…”
Section: Introductionmentioning
confidence: 99%